Determinasi Kualitas Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2023 - Erista Marpaung; Listiorini Listiorini (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study aims to analyze the effect of profit growth, liquidity, and Leverage on profit quality with company size as a moderation variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This research is based on the importance of profit quality as an indicator of real financial performance, as well as the phenomenon of profit management practices that can reduce the quality of financial information. The research method used was quantitative with a causal and associative approach, using secondary data from the financial statements of 65 manufacturing companies over five years. Data analysis techniques include multiple linear regression analysis and moderated regression analysis (MRA) with the help of SPSS software. The results show that profit growth, liquidity, and Leverage have a significant negative effect on the quality of profit. This indicates that the increase in these three variables tends to decrease the quality of profits, which is likely due to profit management practices to maintain the company's financial image. In addition, company size is not able to moderate the relationship between profit growth, liquidity, and Leverage to profit quality. These findings imply that the scale of the company does not affect the strength of the relationship between these variables and the quality of profits. This research makes a theoretical contribution in enriching the accounting literature regarding the factors that affect the quality of profits and the role of company size. Practically, the results of the research can be a reference for company management and investors in improving the transparency and quality of financial reporting.